2012
DOI: 10.1590/s1519-69842012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting the distribution of land snails in the Atlantic Rain Forest of Ilha Grande, Angra dos Reis, RJ, Brazil

Abstract: The distribution and abundance of terrestrial molluscs are affected by environmental factors, but data are lacking for Brazilian land snails. The aim of this study was to understand the relationship between measured environmental factors and the land-snail species composition of two hillsides covered with Atlantic Rain Forest on Ilha Grande. On each hillside, five plots located at 100 m intervals between 100 to 500 m asl were chosen. Each plot was sampled by carrying out timed searches and collecting and sorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…Ciente dessa problemática, o Laboratório de Malacologia Límnica e Terrestre da UERJ iniciou pesquisas sobre a diversidade de moluscos terrestres e gradiente de altitude na Ilha Grande, Rio de Janeiro. Uma parte desta pesquisa resultou em uma dissertação de mestrado (Nunes, 2007, Nunes & Santos 2010, 2012, outra parte integrará a Tese de Doutoramento da primeira autora. …”
Section: Resultsunclassified
“…Ciente dessa problemática, o Laboratório de Malacologia Límnica e Terrestre da UERJ iniciou pesquisas sobre a diversidade de moluscos terrestres e gradiente de altitude na Ilha Grande, Rio de Janeiro. Uma parte desta pesquisa resultou em uma dissertação de mestrado (Nunes, 2007, Nunes & Santos 2010, 2012, outra parte integrará a Tese de Doutoramento da primeira autora. …”
Section: Resultsunclassified
“…Live snails inhabit among leaf litter and below tree trunks laid on the floor were found in rainforest areas in the Tijuca area in Rio de Janeiro. In Ilha Grande specimens were found more frequently between 200 to 500 m asl, corresponding to the most preserved areas with higher humidity, canopy closure and litter depth associated to lesser luminosity and temperature (Nunes and Santos 2012).…”
Section: Geographic Range and Habitatmentioning
confidence: 97%
“…Solaropsis brasiliana (Deshayes 1832) is a species emblematic to Rio de Janeiro State, often found in Ilha Grande (Haas 1953, Santos et al 2010, Nunes and Santos 2012. The taxonomic identification of material preserved in collections is often confused with Solaropsis pilsbryi Ihering 1900 and also with S. gibboni because of the lack of a clear diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of CHOI et al (2004), mathematical modeling using derived ordinary equations found that mortality in young Deroceras reticulatum (Muller, 1774) is more influenced by temperature, while recruitment rates in young individuals and the mortality rate of adults are more influenced by precipitation. Recent work by NUNES & SANTOS (2012) showed that the variables moisture, air temperature, soil temperature and depth of plant litter influence the distribution and abundance of terrestrial gastropods in the Atlantic Forest. Snails depend on high humidity to have an active life (BAKER 1958), being sensitive to desiccation, which tends to restrict their movements (GETZ 1974).…”
Section: 8mentioning
confidence: 99%